INVESTIGATING INTERACTIONAL ACTIVITIES PROMOTING ENGLISH LEARNING AT ATTARBIYATUL ISLAMIYAH ISLAMIC BOARDING SCHOOL IN PAITON PROBOLINGGO - Muhammad Rifa'i (Graduate Program, University of Islam Malang, 2020)
This study was conducted to find out the interactional activities happening in both outside and inside classroom at Attarbiyatul Islamiyah Islamic Boarding School in Paiton Probolinggo. This study used descriptive case study. Two English teachers and two students were selected as the source data through interviewee session. Observation by taking field notes and documentation were conducted to collect more information. The writer analyzed the collected data descriptively through three-stage models; data reduction, data display, and conclusion. Findings yielded three main interactional activities; two interactional activities outside the classroom and interactional activities happening inside the classroom. Face to face conversation which were conducted daily every after Subuh and Midday prayer by making two lines of prayers’ participants facing each other practicing English speaking of any topics. Delivering English speech which was conducted weekly trained students using English in front of public. Interactional activities happening inside the classroom happening by joining the English learning activities with the English teachers focusing on structural development and also still speaking ability performances. The writer can conclude that the daily uses of English as the language target successfully promoted the English learning mainly forming the speaking habit.